Advanced Oxidation Process with Peracetic Acid and Fe(II) for Contaminant Degradation - Kim, Juhee; Zhang, Tianqi; Liu, Wen; Du, Penghui; Dobson, Jordan T.; Huang, Ching-Hua (Environmental Science & Technology, 2019)
Fe(II) is an excellent promoter for advanced oxidation processes (AOPs) because of its environmental ubiquity and low toxicity. This study is among the first to characterize the reaction of peracetic acid (PAA) with Fe(II) ion and apply the Fe(II)/PAA AOP for degradation of micropollutants. PAA reacts with Fe(II) (k = 1.10 × 105–1.56 × 104 M–1 s–1 at pH 3.0–8.1) much more rapidly than H2O2 and outperforms the coexistent H2O2 for reaction with Fe(II). While PAA alone showed minimal reactivity with methylene blue, naproxen, and bisphenol-A, significant abatement (48–98%) of compounds was observed by Fe(II)/PAA at initial pH of 3.0–8.2. The micropollutant degradation by Fe(II)/PAA exhibited two kinetic phases (very rapid then slow) related to PAA and H2O2, respectively. Based on experimental evidence, formation of carbon-centered radicals (CH3C(O)O•, CH3C(O)•, and •CH3), •OH, and Fe(IV) reactive intermediate species from the PAA and Fe(II) reactions in the presence of H2O2 is hypothesized. The carbon-centered radicals and/or Fe(IV) likely played an important role in micropollutant degradation in the initial kinetic phase, while •OH was important in the second reaction phase. The transformation products of micropollutants showed lower model-predicted toxicity than their parent compounds. This study significantly advances the understanding of PAA and Fe(II) reaction and demonstrates Fe(II)/PAA to be a feasible advanced oxidation technology.